Queerly centered : LGBTQA writing center directors navigate the workplace - Webster, Travis (Utah State University Press, 2021)
"Examines intersections among writing center administration and LGBTQA identity, exploring queer directors, their administrative labor, and the implications of their labor in administration. Shows the nuanced and complex labor undertaken but not previously acknowledged in research, even though higher percentages of directors are gay, compared to national averages"--